THE INFLUENCE OF TAX MORALE IN ENCOURAGING TAXPAYER COMPLIANCE IN MICRO, SMALL AND MEDIUM ENTERPRISES (EMPIRICAL STUDY OF MSMES IN MAKASSAR CITY) - Syamsuri Rahim; Sri Rati; Muslim Muslim (SEAN Institute, 2023)
The purpose of this study was to examine the effect of moral tax on MSME taxpayer compliance. This research was conducted in all Micro, Small and Medium Enterprises (MSMEs) in Makassar. The method used is the sampling method (purposive sampling). This method requires taking the number of samples as determined by the researcher as a target that must be met. The sample in this study were 50 actors in the field of MSMEs in Makassar. Methods of data collection using the questionnaire method. Testing the data in this study using the test of moderation regression analysis. Data processing is done using the SPSS program application. The results of this study indicate that tax morale has a significant positive effect on MSME taxpayer compliance, taxpayer demographic moderation has a positive and insignificant influence between moral tax on MSME taxpayer compliance.